Development of Ecotourism Based on Ecosystem Services in the Tanjung Batu Mangrove Ecosystem, Central Sekotong, Indonesia: Pengembangan Ekowisata Berbasis Jasa Ekosistem di Ekosistem Mangrove Tanjung Batu, Sekotong Tengah, Indonesia - M. Alhafizin; Handrayani, Handrayani (Yayasan Siti Widhatul Faeha, 2025)
Mangrove ecosystems provide essential ecological and socio-economic services that support coastal sustainability, yet their potential has not been fully optimized in ecotourism development. This study aims to identify the roles of mangrove ecosystem services, review effective ecotourism models, and formulate development recommendations for the Tanjung Batu Mangrove Area. A Systematic Literature Review (SLR) following the PRISMA 2020 protocol was conducted, and 52 eligible articles were analyzed using thematic synthesis supported by bibliometric mapping. The findings show that regulating and cultural ecosystem services are the most influential in shaping mangrove ecotourism, particularly through shoreline protection, habitat support, and educational value. Community-based ecotourism (CBE), educational tourism, and conservation-oriented approaches emerge as the most effective models across tropical coastal regions. Successful implementation is determined by ecological integrity, community participation, and supportive governance. For Tanjung Batu, integrating these components offers a strategic framework for enhancing tourism potential while strengthening conservation outcomes. This study recommends applying a hybrid community-based and education-focused ecotourism model supported by governance collaboration to ensure long-term ecological resilience and sustainable coastal development.